JOAQUIM MAMEDE´S REPORT ABOUT THE LEGALIZATION OF WOMEN'S JUDO PRACTICE IN BRAZIL (Fiep Bulletin - online, 2014)
"Sports of modern confrontation" between two teams imply violence as "a frugal and legitimate ingredient" (DUNNING, 1992 P.134). In Brazil's last century, according to Mourão and Saraiva, women team sports and body combat in which confrontation was implied were not  advisable and even forbidden by law in order to prevent women's physical integrity as well as to secure the safety of their descendants' procreation. Based on these arguments, the National Council of Sports settled strict rules in 1965 which established women's participation in sports: "Any kind of confrontation and combat practice, soccer, in-door soccer, beach soccer, polo, weight lifting and baseball was not allowed. The power of this law reinforced prejudice against women's participation in the so called masculine sports, nonetheless, judo coachers had not been intimidated by it and stimulated their women practitioners to do martial arts. It is in this scenario that we take profit from the Oral History (FREITAS, 2002) to support the ex-president of the Brazilian Confederation of Judo Joaquim Mamede de Carvalho e Silva whose effort before the National Council of Sports was of immense help in order  to legalize women's judo practice in Brazil. Later on, some other sports modalities took advantage of his interference.
Keywords: Women's judo; Oral History; legalization